Catalyst-free transfer hydrogenation of activated alkenes exploiting isopropanol as the sole and traceless reductant. Issue 2 (12th January 2023) - Das, Tamal Kanti; Rodriguez Treviño, Agustin M.; Pandiri, Sanjay; Irvankoski, Sini; Siitonen, Juha H.; Rodriguez, Sara M.; Yousufuddin, Muhammed; Kürti, László
Abstract : Described herein is an unconventional catalyst-free transfer hydrogenation reaction of activated alkenes using isopropanol as an eco-friendly reductant and solvent. Abstract : Both metal-catalyzed and organocatalytic transfer hydrogenation reactions are widely employed for the reduction of CO and CN bonds. However, selective transfer hydrogenation reactions of CC bonds remain challenging. Therefore, the chemoselective transfer hydrogenation of olefins under mild conditions and in the absence of metal catalysts, using readily available and inexpensive reducing agents ( i.e. primary and secondary alcohols), will mark a significant advancement towards the development of green transfer hydrogenation strategies. Described herein is an unconventional catalyst-free transfer hydrogenation reaction of activated alkenes using isopropanol as an eco-friendly reductant and solvent. The reaction gives convenient synthetic access to a wide range of substituted malonic acid half oxyesters (SMAHOs) in moderate to good yields. Mechanistic investigations point towards an unprecedented hydrogen bond-assisted transfer hydrogenation process.